2019
DOI: 10.1002/ctpp.201800189
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic effects on asymmetric two‐dimensional vortex patterns in a strongly coupled dusty plasma

Abstract: Strongly coupled dusty plasma medium is often described as a viscoelastic fluid that retains its memory. In a flowing dusty plasma medium, vortices of different sizes appear when the flow does not remain laminar. The vortices also merge to transfer energy between different scales. In the present work, we study the effect of viscoelasticity and compressibility over a localized vortex structure and multiple rotational vortices in a strongly coupled viscoelastic dusty plasma medium. In case of single rotating vor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In the past few decades, dusty plasmas have attracted much research attention because they play important roles in many phenomena in the astrophysical environments, the Earth's ionosphere, 2–7 as well as in industrial processes such as semiconductor device manufacturing, plasma etching, materials coating and modification, etc 1,6–9 . As a result, there has been much interest in the theory and applications of dusty plasmas, covering a large range of the physical parameters involved 10–35 . Since the electrons have much higher mobility, inelastic collisions between the electrons and dust grains are much more frequent than that of ions, so that the dust grains are usually highly negatively charged 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few decades, dusty plasmas have attracted much research attention because they play important roles in many phenomena in the astrophysical environments, the Earth's ionosphere, 2–7 as well as in industrial processes such as semiconductor device manufacturing, plasma etching, materials coating and modification, etc 1,6–9 . As a result, there has been much interest in the theory and applications of dusty plasmas, covering a large range of the physical parameters involved 10–35 . Since the electrons have much higher mobility, inelastic collisions between the electrons and dust grains are much more frequent than that of ions, so that the dust grains are usually highly negatively charged 10 …”
Section: Introductionmentioning
confidence: 99%
“…Song et al 22 studied the effect of the plasma temperature on the structures and the dynamics of dust clusters, and found that depending on the discharge power, dust clusters can also be in crystal or liquid states. Existing studies have also considered various internal and external, such as ion and neutral‐particle drag, thermophoretic, radiation pressure, gravitational, etc., forces and other effects on the dynamics and structure of dust grains in a plasma 11–35 …”
Section: Introductionmentioning
confidence: 99%